2017
DOI: 10.1161/circulationaha.116.025080
|View full text |Cite
|
Sign up to set email alerts
|

Factorial Effects of Evolocumab and Atorvastatin on Lipoprotein Metabolism

Abstract: URL: http://www.clinicaltrials.gov. Unique identifier: NCT02189837.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
101
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(108 citation statements)
references
References 38 publications
5
101
1
1
Order By: Relevance
“…This approach sequesters virtually all PCSK9 in the reticuloendothelial system, thus preventing it from binding to the LDL receptor. 5,6 Circulating PCSK9 is derived almost entirely from the liver 7 ; hence, therapeutic approaches that target hepatic production of PCSK9 may offer an alternative to the use of monoclonal antibodies.RNA interference and related RNA silencing pathways provide an opportunity to harness a highly specific endogenous mechanism for regulating gene expression.8 Small interfering RNAs (siRNAs) selectively and catalytically silence the translation of their complementary target messenger RNAs (mRNAs) in a sequence-specific manner through the formation of effector RNAinduced silencing complexes. 9,10 Inclisiran is an investigational, chemically synthesized siRNA molecule that has produced sustained hepatocytespecific, PCSK9-specific RNA silencing in healthy volunteers to 84 days after administration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This approach sequesters virtually all PCSK9 in the reticuloendothelial system, thus preventing it from binding to the LDL receptor. 5,6 Circulating PCSK9 is derived almost entirely from the liver 7 ; hence, therapeutic approaches that target hepatic production of PCSK9 may offer an alternative to the use of monoclonal antibodies.RNA interference and related RNA silencing pathways provide an opportunity to harness a highly specific endogenous mechanism for regulating gene expression.8 Small interfering RNAs (siRNAs) selectively and catalytically silence the translation of their complementary target messenger RNAs (mRNAs) in a sequence-specific manner through the formation of effector RNAinduced silencing complexes. 9,10 Inclisiran is an investigational, chemically synthesized siRNA molecule that has produced sustained hepatocytespecific, PCSK9-specific RNA silencing in healthy volunteers to 84 days after administration.…”
mentioning
confidence: 99%
“…This approach sequesters virtually all PCSK9 in the reticuloendothelial system, thus preventing it from binding to the LDL receptor. 5,6 Circulating PCSK9 is derived almost entirely from the liver 7 ; hence, therapeutic approaches that target hepatic production of PCSK9 may offer an alternative to the use of monoclonal antibodies.…”
mentioning
confidence: 99%
“…Mechanistic studies in healthy subjects showed that alirocumab increased the clearance of intermediate-density lipoprotein (IDL) as well as LDL and there was also an increase in the fractional clearance rate of Lp(a) with no change in the production rate, suggesting increased LDLRs may play a role in the reduction of plasma Lp(a) (19). A study with evolocumab showed similar findings but also showed increased fractional catabolism of very-low-density lipoprotein (VLDL)-apoB and reduced production rate of IDL-apoB suggesting that the clearance of VLDL particles from the circulation may also be increased (20). PCSK9 also interacts with other members of the LDLR superfamily including the VLDL receptor (VLDLR), apolipoprotein E receptor 2 (ApoER2), and lipoprotein receptor-related protein 1 (LRP1), and effects of PCSK9 mAbs to reduce the PCSK9 interaction with these receptors may contribute to increased triglyceride-rich lipoprotein catabolism, and thereby reduction of triglyceride levels, as well as the effects on the LDLR (21).…”
mentioning
confidence: 78%
“…The recent study showed lower levels of fasting and postprandial triglycerides, apoB48 (an indicator of remnant lipoprotein metabolism), and total apoB (a surrogate of apoB100) in individuals carrying loss‐of‐function PCSK9 genetic variants, supporting a role of PCSK9 in the reduction of uptake of apoE‐containing remnant particles as well as LDL 31. Recent kinetic studies in healthy subjects showed that PCSK9 inhibitors decreased fractional production rate of LDL and intermediate‐density lipoprotein, and increased fractional clearance rates of very‐low‐density lipoprotein, intermediate‐density lipoprotein, and LDL particles, which may reflect a much higher expression of hepatic LDLRs than with statin treatment 39, 40. Similarly, lipoprotein (a) levels were also decreased with PCSK9 inhibitors, which was previously not seen with statins 40, 41.…”
Section: Mechanism Of Action Of Pcsk9 Inhibitorsmentioning
confidence: 97%